Broadband frequency translation through time refraction in an epsilon-near-zero material - Yiyu Zhou (Nature Portfolio, 2020)
Here, the authors present an experimental demonstration of adiabatic frequency conversion using the concept of time boundary by exploiting the properties of an ITO film operating near its epsilon-near-zero frequency. They demonstrate a large and controllable shift up to 14.9 THz.